2016
DOI: 10.1097/shk.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PD-1

Abstract: Invariant natural killer T-cells (iNKT) are a subset of T-cells that play a regulatory role in sepsis. Following cecal ligation and puncture (CLP), iNKT cells emigrate from the liver and into the circulation and peritoneum in a manner dependent upon co-inhibitory molecule Programmed Cell Death Receptor 1 (PD-1). We hypothesized that the effect of PD-1 on iNKT cell emigration was dependent upon the direct PD-1:PD-L1 interaction and that PD-1 and PD-L1 would play a role in chemotaxis and chemokine receptor expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…i NKT cells regulate clearance of the peritoneal bacterial septic burden and affect influx of key immune cells. Specifically, within adults, we have noted that this i NKT cell regulation of the immune response to sepsis is controlled by the regulatory checkpoint protein PD-1 ( 16 ), a finding not previously observed in neonates.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…i NKT cells regulate clearance of the peritoneal bacterial septic burden and affect influx of key immune cells. Specifically, within adults, we have noted that this i NKT cell regulation of the immune response to sepsis is controlled by the regulatory checkpoint protein PD-1 ( 16 ), a finding not previously observed in neonates.…”
Section: Introductionmentioning
confidence: 52%
“…The CS model at our institution is modification ( 16 ) of the model previously described by Wynn et al ( 17 ). In brief, a naive WT adult donor mouse (C57BL/6J) was euthanized and cecal contents were harvested.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, Wang et al (106) showed that PMNs from CLP mice and patients diagnosed with severe sepsis exhibited a substantial rise in their PD-L1 expression, correlating with increased morbidity in the septic patients. Additionally, these cells, via direct contact, were capable of inducing a marked increase in lymphocytic cell death/dysfunction (another common feature of the septic animal/patient) as well as altering the migrational functionality of the cell (a dysfunction also noted by Young et al (107) in septic mouse i NKT cells) (22). More recently, Patera et al (53) have further found that peripheral blood PMNs from septic patients that expressed high levels of PD-L1 exhibited a decline in their capacity to phagocytize bacteria, a reduction of CD168 expression and a poor production of TNF-α in response to stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…i NKT-cells are capable of both a Th1 and a Th2 response and interact with a diverse array of immune cells serving to both positively and negatively regulate the immune and inflammatory response i NKT-cells are capable of trafficking both within the liver in response to a sterile injury (74), in and out the lung in response to an infection (75). As well as distally to a septic source in the abdomen (76). i NKT-cells are themselves regulated by co-inhibitory/checkpoint proteins, most notably PD-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation